Methyl viologen responsive proteome dynamics of Anabaena sp. strain PCC7120. Issue 16 (14th July 2014) - Panda, Bandita; Basu, Bhakti; Rajaram, Hema; Kumar Apte, Shree
<x xml:space="preserve">Abstract</x> A proteomic approach was employed to elucidate the response of an agriculturally important microbe, Anabaena sp. strain PCC7120, to methyl viologen (MV). Exposure to 2 μM MV caused 50% lethality (LD50) within 6 h and modified the cellular levels of several proteins. About 31 proteins increased in abundance and 24 proteins decreased in abundance, while 55 proteins showed only a minor change in abundance. Of these, 103 proteins were identified by MS. Levels of proteins involved in ROS detoxification and chaperoning activities were enhanced but that of crucial proteins involved in light and dark reactions of photosynthesis declined or constitutive. The abundance of proteins involved in carbon and energy biogenesis were altered. The study elaborated the oxidative stress defense mechanism deployed by Anabaena, identified carbon metabolism and energy biogenesis as possible major targets of MV sensitivity, and suggested potential biotechnological interventions for improved stress tolerance in Anabaena 7120.